The role of dress in women's transition from Iranians to Iranian-Americans: a socio-psychological analysis - Ghayournejadian, Fatemeh (Kansas State University, 2012)
Acculturation can be a difficult process for many immigrants, and because there is a large number of Iranian immigrants living in the United States (over one million), the focus of this study is to understand how women cope with moving from a country with conservative standards to a more liberal country and the role dress plays in their acculturation process. Specifically, the purpose of this study is to: 1) explore Iranian dress standards and the effect these standards have on Iranian-American women’s lives; 2) gain understanding of the role of dress in women’s transition from Iranians to Iranian-Americans; 3) apply Abraham Maslow’s hierarchy of needs motivational model to the women's acculturation process; and 4) compare two distinct generations of women—women born before the 1979 Islamic Revolution and women born after the Revolution. This study utilized a qualitative approach and collected data through semi-structured interviews with 11 women. The women did not express any traumatic psychological effects caused by the conservative dress standards in Iran. The main impact of the dress standards was the physical discomfort caused by wearing the hijab in hot weather. Dress played a significant role in the women's transitions process. More freedom in dress in the United States has allowed the women to express themselves much more than when they lived in Iran, leading to higher self-esteem and confidence levels. The women expressed a desire to sustain their Iranian heritage, and both generations shared similar perceptions of American dress standards prior to immigrating to the United States. Differences included higher consumption levels by the younger generation and their higher knowledge about the fashion industry and trends. The findings can be useful for Iranian women as they transition to an Iranian-American lifestyle. Additionally, it can also be beneficial to women from other countries who share similar experiences. Furthermore, the results may assist in aiding different organizations which help Iranian women integrate into the U.S. culture. Finally, retailers with target markets similar to the women of this study can use the findings to better understand the habits, needs, motives, and overall consumer behaviors of their clientele.
Keywords: Acculturation; Dress; Iranian-American; Abraham Maslow; Socio-psychological; Women; Behavioral Sciences (0602); Psychology, Behavioral (0384); Social Psychology (0451)